Escitalopram Associated with Priapism: A Rare Case Report - Ankit Halder; Navna Panchami; Gurudas Harshe (Indian Journal of Private Psychiatry)
Priapism is a pathologic condition characterized by the penile erection that persists beyond or is unrelated to sexual stimulation. A 35-year-old male patient presented to the Surgery Emergency Unit with a painful erection for the past 15 hours. This was his third episode in the past 2 months. The last 2 episodes being for 5–6 hours each within intervals of 3 weeks. The patient was diagnosed to be in major depression 6 months back and was placed on escitalopram 10 mg for the first 2 months and then was raised to 20 mg once daily dose. Priapism episodes started 4 months following an increase in dosing. Escitalopram was cross-tapered to nortriptyline over a 1 month. In subsequent follow-up visits for 3 months, the patient experienced no further such episodes. Selective serotonin reuptake inhibitors (SSRIs), mostly escitalopram, are frequently prescribed nowadays for their better tolerability profile. So, while prescribing such medications, psychoeducation of the patients regarding such side effects and meticulous monitoring of the same can be lifesaving many a time.